Enhanced central sympathetic tone induces heart failure with preserved ejection fraction (HFpEF) in rats - Nandi, Shyam S.; Katsurada, Kenichi; Moulton, Michael J.; Zheng, Hong; Patel, Kaushik P. (Frontiers in Physiology, 2023)
Heart failure with a preserved ejection fraction (HFpEF) is a heterogenous clinical syndrome characterized by diastolic dysfunction, concentric cardiac left ventricular (LV) hypertrophy, myocardial fibrosis with a preserved systolic function. However, the underlying mechanisms of disease are not clear. We hypothesize that an enhanced central sympathetic drive is sufficient to induce LV dysfunction and HFpEF in rats. Male Sprague-Dawley rats were subjected to central infusion of either saline controls (Saline) or angiotensin II (Ang II, 20 ng/min, i.c.v) via osmotic mini-pumps for 14 days to elicit enhanced sympathetic drive. Echocardiography and invasive cardiac catheterization were used to measure systolic and diastolic function. Mean arterial pressure, heart rate, left ventricular end diastolic pressure (LVEDP), as well as ±dP/dt changes in responses to isoproterenol (0.5 μg/kg, iv) were measured. Central infusion of Ang II resulted in increased sympatho-excitation with a consequent increase in blood pressure. Although the ejection fraction was comparable between the groups, there was a decrease in E/A ratio (Saline: 1.5 ± 0.2 vs. Ang II: 1.2 ± 0.1). LVEDP was significantly increased in Ang II treated group (Saline: 1.8 ± 0.2 vs. Ang II: 4.6 ± 0.5). The increase in +dP/dt to isoproterenol was not significantly different between the groups, but the response in -dP/dt was significantly lower in Ang II-infused rats (Saline: -11,765 ± 708 mmHg/s vs. Ang II: -8,581 ± 661). Ang II-infused rats demonstrated increased heart to body weight ratio, cardiomyocyte hypertrophy and fibrosis. There were elevated levels of atrial natriuretic peptide and interleukin-6 in the Ang II-infused group. In conclusion, central infusion of Ang II in rats induces sympatho-excitation with concurrent diastolic dysfunction, pathological cardiac concentric hypertrophy and cardiac fibrosis. This novel model of centrally mediated sympatho-exciation demonstrates characteristic diastolic dysfunction in rats representing a potentially useful preclinical murine model of HFpEF to investigate various altered underlying mechanisms during HFpEF in future studies.